Cachette - Lee, Hui Min (2015)
Since young, I have been found of travelling. I love the idea of exploring new places with the ease of baggage over the shoulders and little care needed to worry about the security of my belongings. Nevertheless, being in a foreign place, letting your guards down puts you at risk of being targeted by pickpockets. Hence distributing valuables into smaller pouches and locating them separately becomes a common practice. However, doing this on a day-to-day basis can be a nuisance, having to yank out folded notes from the tiny wallet hidden deep in your pockets every now and then just to pay for the little things you want to get on the street. Bigger and longer wallets are impractical to carry for travelling as well as they can’t be kept in the pockets of your garment without exposing themselves and risk being stolen. Hidden pockets underneath garment are dreadful as well as they causes much discomfort to the body.Overly-cautious and paranoid behaviour also put you at risk of theft, as the act of patting your pockets and checking your wallets in public are indicating to thieves lurking on the street of the whereabouts of your belonging. Having seen television show featuring ancient drama characters and fictional detective characters who can pull out various items from underneath their sleeve and coat while remaining gracefully light, inspires me to create garments and accessories that can perhaps works in a similar manner. With such garment meant the ease of carrying and watching over bags and hence a hands-free and more carefree travel experience. This is how I get inspired to start off this anti-theft project.